The Relationship between Rewards and Punishments in Islamic Religious Education Learning and the Emotional Intelligence - Hairil Anwar; Sapiudin Shidiq (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This research aims to determine the relationship between giving rewards and the emotional intelligence of class XII Computer Engineering Network students at SMKN 2 Kisaran, the relationship between giving punishment and the emotional intelligence of class. The type of research conducted is descriptive quantitative research. This study used several research method instruments, namely observation, documentation, and questionnaires. Meanwhile, the author used quantitative data analysis, which emphasizes statistical data in the form of numbers systematically tabulated using multiple-count correlation analysis techniques. The results of this study indicate that: 1) There is a significant relationship between the provision of rewards in Islamic Religious Education learning with the emotional intelligence of class XII TKJ students at SMKN 2 Kisaran with the calculated t for variable X1 (2.859) greater than the t table (1.985) so it is said to be significant. 2) There is a significant relationship between the provision of punishment in Islamic Religious Education learning with the emotional intelligence of class XII TKJ students at SMKN 2 Kisaran with the calculated t for variable X2 (2.210) greater than the t table (1.985) so it is said to be significant. 3) There is a significant relationship simultaneously between the provision of rewards and punishments with emotional intelligence in PAI learning conducted at SMKN 2 Kisaran, with an Ftable value of (3.088) then Fcount (4.330) is greater than Ftable (3.088) with a significant value (0.001) smaller than (0.05) so that the decision of all independent variables is accepted. Thus it can be concluded that there is a significant relationship between rewards and punishments with students' emotional intelligence.